Criminal Liability Against Corporations in Payment of Wages Under the Provisions of Legislation - Ida Hanifah (International Journal Reglement & Society (IJRS), 2022)
As a legal subject, corporations have responsibilities as regulated in Law No. 13 of 2003. Manpower is either a legal entity or not. In the Manpower Act, corporate responsibility consists of two, namely; administrative sanctions as well as criminal sanctions. The criminal sanctions applied are in the form of imprisonment and fines. The criminal liability of corporations used by the law is in the form of "Corporations act, responsible management", due to the cumulative criminal sanctions that exist in the law. The means of renewal in the context of development can be interpreted as channeling human activities that lead to development. So, the community has directions for channeling development in the manpower sector in order to realize national development which will be aimed at supervising, fostering, and regulating all activities in the workforce so that justice is achieved. This supervision is based on appropriate labor legislation and adjustments to the rapid growth and development of development in order to anticipate the pressure on the supply of labor, and the level of protection of the workforce.